Inclusive Education and Physical Education in Spain: A Qualitative Analysis of Teachers’ Perspectives - Pablo Saiz-González; Sara de la Fuente-González; Jacob Sierra-Díaz; Pablo Uría-Valle (Education Sciences)
This study examined the perceptions of physical education teachers regarding inclusive education in their classes. A qualitative, cross-sectional design was employed, using a digital survey with an open-ended question designed to explore barriers and needs in implementing inclusive practices. Thematic content analysis was conducted to identify key themes from the responses. Seventy-five in-service physical education teachers from diverse educational contexts in Spain participated, sharing their experiences and challenges. Participants expressed genuine interest in receiving training and incorporating inclusive principles into their practices. However, structural limitations, such as high student–teacher ratios and insufficient specialized resources, significantly hindered their ability to implement these strategies effectively. Persistent challenges, including excessive workloads and the lack of support personnel, were reported, leading to frustration in their efforts to provide an equitable education for all students. Although focused on the Spanish context, these findings resonate with international research, highlighting similar structural barriers to inclusive education. This study underscores the need for ongoing, discipline-specific training for physical education teachers, supported by strong institutional commitments to ensure the provision of adequate human and material resources. Without such support, the burden on teachers remains disproportionate and ultimately unfair, hindering progress towards a truly inclusive educational environment.